The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1538-7836.2007.02818.x
|View full text |Cite
|
Sign up to set email alerts
|

ABO(H) blood groups and vascular disease: a systematic review and meta‐analysis

Abstract: To cite this article: Wu O, Bayoumi N, Vickers MA, Clark P. ABO(H) blood groups and vascular disease: a systematic review and meta-analysis. 2008; 6: 62-9. Summary. Background: Associations between vascular disease and ABO(H) blood groups have a long history, but no consensus exists regarding its magnitude and significance, or whether it relates to all disorders equally. An accurate calculation of risk would allow direct assessment of whether the effects of non-O status on thrombosis risk are of the magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
329
7
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(372 citation statements)
references
References 76 publications
25
329
7
5
Order By: Relevance
“…23 Of particular interest is the association of O histo-blood groups with a reduced risk of myocardial infarction, peripheral vascular disease, stroke and venous thromboembolism. 24 These findings are only partially explained by the lower levels of factor VIIIc and Willebrand factor in the O blood types as compared with other blood types. 25 The exact mechanism is not entirely understood.…”
Section: Discussionmentioning
confidence: 94%
“…23 Of particular interest is the association of O histo-blood groups with a reduced risk of myocardial infarction, peripheral vascular disease, stroke and venous thromboembolism. 24 These findings are only partially explained by the lower levels of factor VIIIc and Willebrand factor in the O blood types as compared with other blood types. 25 The exact mechanism is not entirely understood.…”
Section: Discussionmentioning
confidence: 94%
“…On this note, the influence of ABO-system blood types on the nervous system has been a largely unexplored research area. Despite the association which has been frequently reported between 'O' and non-'O' blood types and cardiovascular risk factors (Carpeggiani et al, 2010;Wu et al, 2008;Yang et al, 2014), recent findings suggest that other, non-vasculogenic mechanisms might exist, such as, for instance, the involvement of glycosyltransferase enzymes encoded by the ABO genetic locus (Alexander et al, 2014). In a retrospective and explorative fashion, we carried out a voxel-based morphometric analysis of the differences of whole-brain GM volumes between a subgroup of healthy adults with 'O' blood type and comparable subgroups having other blood types.…”
Section: -Discussionmentioning
confidence: 99%
“…Consistently with higher plasma levels of a clotting-inducing factor, non-'O' adults carry a larger number of cardiovascular risk factors (Carpeggiani et al, 2010). Based on this evidence, many studies have investigated the association between blood type and the occurrence of vascular events affecting the brain (Wu et al, 2008).…”
Section: -Introductionmentioning
confidence: 99%
“…34 Association between non-O blood group carriership with myocardial infarction recently has been confirmed in a metaanalysis of predominantly retrospective studies comprising 8220 cases and 509 009 controls. 35 Historically, ABO has been one of the first-available genetically determined markers, and there are numerous reports of associations with various phenotypes. Some of these studies had small sample sizes and showed only modest statistical significance, adding to skepticism about these findings.…”
Section: Discussionmentioning
confidence: 99%